EDUCATORS’ ATTITUDE TO THE SPREAD OF TEACHER COMPETENCES - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2009)
The importance of competences attached to teacher’s profession is gaining better perception in the context of the 21st century challenges. Teacher competences are often associated to learning / teaching achievements, communication, teacher knowledge and teacher personality. These are the highest contours of teacher competences. Encoding the research data according to categories, they are ranked in the following order: communication, education process, and teacher’s preparedness, personality and achievements. It was observed that communication and achievements are often linked with school learners, whereas personality is related to an educator. The content of categories shows that teachers refer to classical paradigm of education, which is grounded on direct contribution of an educator to school learners’ learning. New education technologies and learners achievements are presented only episodically. Structural generalisation of the research data revealed the fact that teachers include all the elements of competence in the general context; however, only one respondent refers to them all jointly. The research confirms the vitality of competence structure and its reality. In terms of content, the attitudes of teachers are more similar to the conception of competences presented in the ‘Outline of the national qualifications framework of Lithuania’, where personal, social and ethic competences are distinguished. Teacher competences are often of fragment character and reflect the structure of competence in a more general way with insufficient escalation of 15its content. Therefore, education of competences is becoming an urgent problem, whose timely solving may positively affect implementation modern goals of education.